SISTEM PENDUKUNG PEMILIHAN PEKERJAAN MENGGUNAKAN METODE APRIORI BERDASARKAN KORELASI JURUSAN DENGAN IPK UNTUK MENGETAHUI PEKERJAAN YANG TEPAT - Achmad Fauzi; Iis Joice Susanti Marpaung; Akim Manaor Hara Pardede (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2018)
The main problem used by college graduates is how to get results quickly and precisely in accordance with their scientific fields, of course it can be accessed by various factors, accreditation of universities, majors, GPA income, hard skills, soft skills, attitude, and work experience. In the database for alumni of higher education, alumni from STMIK Kaputama-Binjai are very diverse, which have only been stored without further data processing. With the data obtained from the database, namely data to collect alumni data by applying data mining to get new information. By implementing data mining on data with alumni with a priori algorithm, can know the confidence and great support for majors and GPA profits. And decisions can be a Decision Support Work, students who will graduate and alumni have the right job information in accordance with the GPA department and income. From the rules found, it can be concluded that STMIK alumni, especially Information Systems Study Program who have a GPA B (Good) will work in the field of Financing.